ARK: GPU-driven Code Execution for Distributed Deep Learning - Hwang, Changho; Shu, Ran; Cheng, Peng; Xiong, Yongqiang; Park, KyoungSoo (NSDI, 2023)
Modern state-of-the-art deep learning (DL) applications tend to scale out to a large number of parallel GPUs. Unfortunately, we observe that the collective communication overhead across GPUs is often the key limiting factor of performance for distributed DL. It under-utilizes the networking bandwidth by frequent transfers of small data chunks, which also incurs a substantial I/O overhead on GPU that interferes with computation on GPU. The root cause lies in the inefficiency of CPU-based communication event handling as well as the inability to control the GPU's internal DMA engine with GPU threads. To address the problem, we propose a GPU-driven code execution system that leverages a GPU-controlled hardware DMA engine for I/O offloading. Our custom DMA engine pipelines multiple DMA requests to support efficient small data transfer while it eliminates the I/O overhead on GPU cores. Unlike existing GPU DMA engines initiated only by CPU, we let GPU threads to directly control DMA operations, which leads to a highly efficient system where GPUs drive their own execution flow and handle communication events autonomously without CPU intervention. Our prototype DMA engine achieves a line-rate from a message size as small as 8KB (3.9x better throughput) with only 4.3us of communication latency (9.1x faster) while it incurs little interference with computation on GPU, achieving 1.8x higher all-reduce throughput in a real training workload.